A quantum dot diffusion plate and preparation method thereof
By adopting a three-layer structure design in the quantum dot diffusion plate, PEI polymer microspheres coat the quantum dots and form a stable network structure, combined with PBT resin and other additives, the problem of difficulty in uniform dispersion and low luminous efficiency during the preparation process is solved, and efficient and stable light propagation and excellent comprehensive performance are achieved.
Patent Information
- Application Number
- CN202411352635.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-09-26
AI Technical Summary
In the preparation process, existing quantum dot diffusion plates are difficult to disperse quantum dots evenly, resulting in a decrease in luminous efficiency and stability. The poor combination of PBT resin with quantum dots affects light propagation and barrier properties.
The three-layer structure of quantum dot diffusion plate is designed, in which the intermediate layer uses PEI polymer microspheres to coat the surface carboxylated oil-soluble CdSe/ZnS quantum dots, and forms a stable network structure through glutaraldehyde, combining PBT resin and other additives to improve the stability and light propagation performance of the quantum dots.
It realizes uniform dispersion and stable coating of quantum dots, improves luminescence efficiency and stability, and enhances water-oxygen barrier properties, light transmittance and mechanical strength, and has excellent comprehensive performance.
Smart Images

Figure CN119217828B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of diffusion plates, and specifically to a quantum dot diffusion plate and a preparation method thereof. Background Art
[0002] Quantum dots are a type of nano-scale semiconductor. By applying a certain electric field or light pressure to this nano-semiconductor material, they will emit light of a specific frequency. Existing technologies often combine quantum dot technology with light diffusers to make quantum dot diffusers. However, since quantum dots are very sensitive to heat, oxygen and water, there are the following difficulties that need to be overcome in the preparation process: first, how to evenly disperse the quantum dots in the polymer masterbatch; second, the quantum yield of quantum dots will decrease during high-temperature granulation or extrusion processes, which will in turn affect the luminous efficiency and stability.
[0003] PEI is the abbreviation of polyethyleneimine, which is a polymer material with a high nitrogen atom content. Because of the large number of amine groups (-NH2) in its molecular structure, PEI has good adhesion and adsorption properties. When combined with quantum dots, PEI can act as a surface modifier to help fix the quantum dots on the target surface and provide better dispersion and stability. By combining PEI and quantum dots, the stability, biocompatibility and fluorescence efficiency of quantum dots can be improved.
[0004] PBT resin is a milky white, translucent, semi-crystalline thermoplastic polyester with high heat resistance. It is an excellent engineering plastic with many advantages such as high mechanical strength, good fatigue resistance, good dimensional stability, and good solvent resistance. It is widely used in electronics, automobiles, home appliances and other fields.
[0005] Simply adding PBT resin to the quantum dot diffusion plate will still cause brightness decay and poor luminous efficiency as the quantum dots become inactive, because the quantum dots cannot be stably and evenly dispersed in the PBT resin. Therefore, how to combine PBT resin with quantum dots to obtain a quantum dot diffusion plate with good water and oxygen barrier properties, high luminous efficiency, stable luminescence, high light transmittance, high heat resistance, high mechanical strength, fatigue resistance and other excellent indicators and good comprehensive performance is a topic worth studying, but no reports on this have been seen so far. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a quantum dot diffusion plate, including an upper diffusion plate, an intermediate diffusion plate and a lower diffusion plate, wherein the upper diffusion plate and the lower diffusion plate are located on both sides of the intermediate diffusion plate, and the intermediate diffusion plate includes the following components in parts by mass: 74 to 88 parts of PBT resin, 1 to 3 parts of PEI polymer microspheres, 0.1 to 0.5 parts of surface carboxylation oil-soluble CdSe / ZnS quantum dots, 0.05 to 0.09 parts of glutaraldehyde, 10 to 20 parts of ethanol, 0.3 to 0.7 parts of antioxidants, 0.03 to 0.07 parts of mineral oil, 0.3 to 0.7 parts of light stabilizers, 0.2 to 0.9 parts of ultraviolet absorbers, and 0.02 to 0.04 parts of whitening agents.
[0007] Preferably, the upper diffuser plate and the lower diffuser plate have the same components, and the upper diffuser plate or the lower diffuser plate includes the following components in parts by mass: 79 to 89 parts of PBT resin, 7 to 11 parts of PEI polymer microspheres, 3 to 7 parts of γ-aminopropyltriethoxysilane, 0.4 to 1.2 parts of antioxidant, 0.03 to 0.07 parts of mineral oil, 0.3 to 0.7 parts of light stabilizer, 0.2 to 0.9 parts of ultraviolet absorber, and 0.07 to 0.13 parts of whitening agent.
[0008] Preferably, the antioxidant is at least one of antioxidant 1024, antioxidant 1010 or antioxidant 1076.
[0009] Preferably, the mineral oil is silicone oil or liquid paraffin.
[0010] Preferably, the light stabilizer is any one or more selected from light stabilizer 622, light stabilizer 770, and light stabilizer 944.
[0011] Preferably, the ultraviolet absorber is selected from one or more of the ultraviolet absorbers UV-327, UV-329, and UV-531.
[0012] Preferably, the brightener is fluorescent brightener CBS-127.
[0013] The present invention also provides a method for preparing a quantum dot diffusion plate, comprising the following steps:
[0014] Add 10 to 20 parts of ethanol to a reaction container, then add 0.1 to 0.5 parts of surface carboxylation oil-soluble CdSe / ZnS quantum dots to the ethanol, perform ultrasonication for 10 to 30 minutes to ensure that the surface carboxylation oil-soluble CdSe / ZnS quantum dots are uniformly dispersed in the ethanol, then mix 1 to 3 parts of PEI polymer microspheres and 0.05 to 0.09 parts of glutaraldehyde and add the mixture to the reaction container, stir while adding to ensure that the surface carboxylation oil-soluble CdSe / ZnS quantum dots are uniformly coated by the PEI polymer microspheres to obtain a mixed solution, centrifuge the mixed solution, collect a precipitate, wash the precipitate with ethanol for multiple times, and then dry the precipitate for standby use;
[0015] The precipitate is mixed with 74-88 parts of PBT resin, 0.3-0.7 parts of antioxidant, 0.03-0.07 parts of mineral oil, 0.3-0.7 parts of light stabilizer, 0.2-0.9 parts of ultraviolet absorber, and 0.02-0.04 parts of brightener to obtain a mixture a;
[0016] 79-89 parts of PBT resin, 7-11 parts of PEI polymer microspheres, 3-7 parts of γ-aminopropyltriethoxysilane, 0.4-1.2 parts of antioxidant, 0.03-0.07 parts of mineral oil, 0.3-0.7 parts of light stabilizer, 0.2-0.9 parts of ultraviolet absorber, and 0.07-0.13 parts of brightener are uniformly mixed to obtain a mixture b;
[0017] Mixture a and mixture b are put into a single screw extruder for heating and melting, and three-layer co-extrusion and embossing are performed to obtain a finished product;
[0018] Among them, the temperatures of each zone of the single-screw extruder are: zone one temperature is 190-200°C, zone two temperature is 210-220°C, zone three temperature is 220-230°C, zone four temperature is 220-230°C, zone five temperature is 230-240°C, zone six temperature is 230-240°C, zone seven temperature is 220-230°C, and the die head temperature is 215-225°C.
[0019] Preferably, the centrifuge speed during centrifugal separation of the mixed solution is 2000-4000 rpm.
[0020] The beneficial effects are as follows: the present application provides a quantum dot diffusion plate including three layers, upper, middle and lower, which can more effectively disperse and homogenize light, and each layer can scatter light once. Through multi-layer scattering, the distribution of light is more uniform; the middle layer diffusion plate uniformly coats the surface carboxylation oil-soluble CdSe / ZnS quantum dots through PEI polymer microspheres to improve the stability of the quantum dots, and improve the fluorescence intensity and quantum yield; by adding cross-linking agent glutaraldehyde, a stable network structure is formed between the surface carboxylation oil-soluble CdSe / ZnS quantum dots and the PEI polymer microspheres, so that the surface carboxylation oil-soluble CdSe / ZnS quantum dots are more firmly combined with the surface of the PEI polymer microspheres; and the selected PEI polymer microspheres have good compatibility with the PBT resin, so that the PEI polymer After the microspheres are uniformly coated with carboxylated oil-soluble CdSe / ZnS quantum dots on the surface, they are easier to disperse evenly in the PBT resin, making the entire middle layer diffuser plate emit more uniform light. At the same time, tests have found that the refractive index of the quantum dot polymer composite microspheres formed after the PEI polymer microspheres are uniformly coated with carboxylated oil-soluble CdSe / ZnS quantum dots on the surface is 1.5463, which is slightly different from the refractive index of the PBT resin of 1.5613. Therefore, the prepared middle layer diffuser plate can simultaneously obtain higher transmittance and haze. In short, the quantum dot diffuser plate prepared in this application has the advantages of stable luminescence, high transmittance, high mechanical strength, fatigue resistance, etc. while maintaining high water and oxygen barrier properties and luminescence efficiency. It combines the advantages of quantum dot diffuser plates and PBT resins and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0022] Figure 1 The microstructure of the present application observed by scanning electron microscopy (SEM);
[0023] Figure 2 This is the thermal gravimetric analysis (TGA) decomposition temperature curve of the quantum dot diffuser plate. DETAILED DESCRIPTION
[0024] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand the present invention more clearly.
[0025] The following embodiments are only used to illustrate the present invention, but are not limited to the scope of the present invention. Based on the specific embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work belong to the protection scope of the present invention.
[0026] In the examples of the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art; in the examples of the present invention, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art.
[0027] Source of raw materials:
[0028] PBT resin, purchased from Dongguan Kaixili Plastic Raw Materials Co., Ltd.;
[0029] PEI polymer microspheres were purchased from Xi'an Qiyue Biotechnology Co., Ltd.;
[0030] Surface carboxylation oil-soluble CdSe / ZnS quantum dots were purchased from Shanghai Shuna Biotechnology Co., Ltd.;
[0031] Glutaraldehyde was purchased from Shandong Xinrong Chemical Co., Ltd.;
[0032] Ethanol was purchased from Guangzhou Dongzhen Chemical Technology Co., Ltd.;
[0033] γ-Aminopropyltriethoxysilane was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0034] Antioxidants were purchased from Shandong Xuxiang Chemical Co., Ltd.
[0035] Silicone oil was purchased from Jinan Xuchuang Chemical Technology Co., Ltd.
[0036] Liquid paraffin was purchased from Hefeng New Energy Co., Ltd.;
[0037] Light stabilizer, purchased from Shanghai Tiandui New Materials Co., Ltd.;
[0038] UV absorber, purchased from Jinan Xiangfeng Weiye Chemical Co., Ltd.;
[0039] Fluorescent brightener CBS-127, purchased from Guangzhou Yuanda New Materials Co., Ltd.;
[0040] The remaining reagents are commercially available.
[0041] Example 1
[0042] This embodiment provides a quantum dot diffusion plate, comprising an upper diffusion plate, an intermediate diffusion plate and a lower diffusion plate, wherein the upper diffusion plate and the lower diffusion plate are located on both sides of the intermediate diffusion plate;
[0043] The intermediate diffuser plate includes the following components by weight: 81 parts of PBT resin, 2 parts of PEI polymer microspheres, 0.3 parts of surface carboxylated oil-soluble CdSe / ZnS quantum dots, 0.07 parts of glutaraldehyde, 15 parts of ethanol, 0.5 parts of antioxidant, 0.05 parts of mineral oil, 0.5 parts of light stabilizer, 0.55 parts of ultraviolet absorber, and 0.03 parts of whitening agent;
[0044] The upper diffuser plate and the lower diffuser plate have the same composition, and the upper diffuser plate or the lower diffuser plate includes the following components in parts by mass: 84 parts of PBT resin, 9 parts of PEI polymer microspheres, 5 parts of γ-aminopropyl triethoxysilane, 0.8 parts of antioxidant, 0.05 parts of mineral oil, 0.5 parts of light stabilizer, 0.55 parts of ultraviolet absorber, and 0.1 parts of brightener;
[0045] The antioxidant is antioxidant 1024, the mineral oil is silicone oil, the light stabilizer is light stabilizer 622, the ultraviolet absorber is ultraviolet absorber UV-327, and the brightener is fluorescent brightener CBS-127;
[0046] The quantum dot diffusion plate is prepared according to the following steps:
[0047] 15 parts of ethanol are added to the reaction container, and then 0.3 parts of surface carboxylation oil-soluble CdSe / ZnS quantum dots are added to the ethanol, and ultrasonication is performed for 20 minutes to ensure that the surface carboxylation oil-soluble CdSe / ZnS quantum dots are uniformly dispersed in the ethanol, and then 2 parts of PEI polymer microspheres and 0.07 parts of glutaraldehyde are mixed and added to the reaction container, and stirring is performed while adding to ensure that the PEI polymer microspheres are uniformly coated with the surface carboxylation oil-soluble CdSe / ZnS quantum dots to obtain a mixed solution, and the mixed solution is centrifuged to collect a precipitate, and the precipitate is washed with ethanol for 5 times, and then the precipitate is dried for standby use;
[0048] The precipitate was mixed with 84 parts of PBT resin, 0.5 parts of antioxidant, 0.05 parts of mineral oil, 0.5 parts of light stabilizer, 0.55 parts of ultraviolet absorber and 0.03 parts of brightener to obtain a mixture a;
[0049] 84 parts of PBT resin, 9 parts of PEI polymer microspheres, 5 parts of γ-aminopropyltriethoxysilane, 0.8 parts of antioxidant, 0.05 parts of mineral oil, 0.5 parts of light stabilizer, 0.55 parts of ultraviolet absorber, and 0.1 parts of brightener are uniformly mixed to obtain a mixture b;
[0050] Mixture a and mixture b are put into a single screw extruder for heating and melting, and three-layer co-extrusion and embossing are performed to obtain a finished product;
[0051] Among them, the temperatures of each zone of the single-screw extruder are: zone one temperature is 195°C, zone two temperature is 215°C, zone three temperature is 225°C, zone four temperature is 225°C, zone five temperature is 235°C, zone six temperature is 235°C, zone seven temperature is 225°C, and the die head temperature is 220°C.
[0052] Example 2
[0053] This embodiment provides a quantum dot diffusion plate, comprising an upper diffusion plate, an intermediate diffusion plate and a lower diffusion plate, wherein the upper diffusion plate and the lower diffusion plate are located on both sides of the intermediate diffusion plate;
[0054] The intermediate diffuser plate includes the following components by weight: 88 parts of PBT resin, 1 part of PEI polymer microspheres, 0.1 parts of surface carboxylated oil-soluble CdSe / ZnS quantum dots, 0.05 parts of glutaraldehyde, 10 parts of ethanol, 0.3 parts of antioxidant, 0.03 parts of mineral oil, 0.3 parts of light stabilizer, 0.2 parts of ultraviolet absorber, and 0.02 parts of whitening agent;
[0055] The upper diffuser plate and the lower diffuser plate have the same composition, and the upper diffuser plate or the lower diffuser plate includes the following components in parts by mass: 89 parts of PBT resin, 7 parts of PEI polymer microspheres, 3 parts of γ-aminopropyl triethoxysilane, 0.4 parts of antioxidant, 0.03 parts of mineral oil, 0.3 parts of light stabilizer, 0.2 parts of ultraviolet absorber, and 0.07 parts of brightener;
[0056] The antioxidant is antioxidant 1010, the mineral oil is liquid paraffin, the light stabilizer is light stabilizer 770, the ultraviolet absorber is ultraviolet absorber UV-329, and the brightener is fluorescent brightener CBS-127;
[0057] The quantum dot diffusion plate is prepared according to the following steps:
[0058] Add 10 parts of ethanol to the reaction container, then add 0.1 parts of surface carboxylation oil-soluble CdSe / ZnS quantum dots to the ethanol, ultrasonicate for 10 minutes to ensure that the surface carboxylation oil-soluble CdSe / ZnS quantum dots are uniformly dispersed in the ethanol, then mix 1 part of PEI polymer microspheres and 0.05 parts of glutaraldehyde and add them to the reaction container, stir while adding to ensure that the PEI polymer microspheres are uniformly coated with the surface carboxylation oil-soluble CdSe / ZnS quantum dots to obtain a mixed solution, centrifuge the mixed solution, collect the precipitate, wash the precipitate with ethanol for multiple times, and then dry the precipitate for standby use;
[0059] The precipitate is mixed with 88 parts of PBT resin, 0.3 parts of antioxidant, 0.03 parts of mineral oil, 0.3 parts of light stabilizer, 0.2 parts of ultraviolet absorber and 0.02 parts of brightener to obtain a mixture a;
[0060] 89 parts of PBT resin, 7 parts of PEI polymer microspheres, 3 parts of γ-aminopropyltriethoxysilane, 0.4 parts of antioxidant, 0.03 parts of mineral oil, 0.3 parts of light stabilizer, 0.2 parts of ultraviolet absorber, and 0.07 parts of brightener are uniformly mixed to obtain a mixture b;
[0061] Mixture a and mixture b are put into a single screw extruder for heating and melting, and three-layer co-extrusion and embossing are performed to obtain a finished product;
[0062] Among them, the temperatures of each zone of the single-screw extruder are: zone 1 temperature is 190°C, zone 2 temperature is 210°C, zone 3 temperature is 220°C, zone 4 temperature is 220°C, zone 5 temperature is 230°C, zone 6 temperature is 230°C, zone 7 temperature is 220°C, and the die head temperature is 215°C.
[0063] Example 3
[0064] This embodiment provides a quantum dot diffusion plate, comprising an upper diffusion plate, an intermediate diffusion plate and a lower diffusion plate, wherein the upper diffusion plate and the lower diffusion plate are located on both sides of the intermediate diffusion plate;
[0065] The intermediate diffuser plate includes the following components by weight: 74 parts of PBT resin, 3 parts of PEI polymer microspheres, 0.5 parts of surface carboxylated oil-soluble CdSe / ZnS quantum dots, 0.09 parts of glutaraldehyde, 20 parts of ethanol, 0.7 parts of antioxidant, 0.07 parts of mineral oil, 0.7 parts of light stabilizer, 0.9 parts of ultraviolet absorber, and 0.04 parts of whitening agent;
[0066] The upper diffuser plate and the lower diffuser plate have the same composition, and the upper diffuser plate or the lower diffuser plate includes the following components in parts by mass: 79 parts of PBT resin, 11 parts of PEI polymer microspheres, 7 parts of γ-aminopropyl triethoxysilane, 1.2 parts of antioxidant, 0.07 parts of mineral oil, 0.7 parts of light stabilizer, 0.9 parts of ultraviolet absorber, and 0.13 parts of brightener;
[0067] The antioxidant is antioxidant 1076, the mineral oil is silicone oil, the light stabilizer is light stabilizer 944, the ultraviolet absorber is ultraviolet absorber UV-531, and the brightener is fluorescent brightener CBS-127;
[0068] The quantum dot diffusion plate is prepared according to the following steps:
[0069] Add 20 parts of ethanol to a reaction container, then add 0.5 parts of surface carboxylation oil-soluble CdSe / ZnS quantum dots to the ethanol, perform ultrasonication for 30 minutes to ensure that the surface carboxylation oil-soluble CdSe / ZnS quantum dots are uniformly dispersed in the ethanol, then mix 3 parts of PEI polymer microspheres and 0.09 parts of glutaraldehyde and add them to the reaction container, stir while adding to ensure that the PEI polymer microspheres uniformly cover the surface carboxylation oil-soluble CdSe / ZnS quantum dots to obtain a mixed solution, centrifuge the mixed solution, collect a precipitate, wash the precipitate with ethanol for multiple times, and then dry the precipitate for standby use;
[0070] The precipitate is mixed with 74 parts of PBT resin, 0.7 parts of antioxidant, 0.07 parts of mineral oil, 0.7 parts of light stabilizer, 0.9 parts of ultraviolet absorber and 0.04 parts of brightener to obtain a mixture a;
[0071] 79 parts of PBT resin, 11 parts of PEI polymer microspheres, 7 parts of γ-aminopropyltriethoxysilane, 1.2 parts of antioxidant, 0.07 parts of mineral oil, 0.7 parts of light stabilizer, 0.9 parts of ultraviolet absorber, and 0.13 parts of brightener are mixed to obtain a mixture b;
[0072] Mixture a and mixture b are put into a single screw extruder for heating and melting, and three-layer co-extrusion and embossing are performed to obtain a finished product;
[0073] Among them, the temperatures of each zone of the single-screw extruder are: zone one temperature is 190-200°C, zone two temperature is 210-220°C, zone three temperature is 220-230°C, zone four temperature is 220-230°C, zone five temperature is 230-240°C, zone six temperature is 230-240°C, zone seven temperature is 220-230°C, and the die head temperature is 215-225°C.
[0074] Comparative Example 1
[0075] The difference between this comparative example and Example 1 is that 81 parts of PBT resin in Example 1 are replaced by 81 parts of GPPS during the preparation of the intermediate diffusion plate, and the other components and experimental steps are the same as those in Example 1.
[0076] Comparative Example 2
[0077] The difference between the comparative example and the example one is that in the process of preparing the intermediate diffusion plate, 0.3 parts of oil-soluble CdSe / ZnS quantum dots are used to replace 0.3 parts of surface carboxylated oil-soluble CdSe / ZnS quantum dots in the example one, and the other ingredients and experimental steps are the same as those in the example one.
[0078] Comparative Example 3
[0079] The difference between this comparative example and Example 1 is that in the process of preparing the intermediate diffusion plate, 0.3 parts of surface carboxylation oil-soluble CdSe / ZnS quantum dots are increased to 0.37 parts, and glutaraldehyde is not added. Other components and experimental steps are the same as those in Example 1.
[0080] Comparative Example 4
[0081] The difference between this comparative example and Example 1 is that in the process of preparing the upper and lower diffusion plates, 84 parts of GPPS resin are used to replace 84 parts of PBT resin in Example 1, and other components and experimental steps are the same as those in Example 1.
[0082] Comparative Example 5
[0083] The difference between this comparative example and Example 1 is that in the process of preparing the upper and lower diffusion plates, 9 parts of PEI polymer microspheres are increased to 14 parts, and γ-aminopropyltriethoxysilane is not added. The other ingredients and experimental steps are the same as those in Example 1.
[0084] Comparative Example 6
[0085] This comparative example is a quantum dot diffusion plate produced by Nantong Chuangyida New Materials Co., Ltd., product model CPQ18B.
[0086] The diffuser plates prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were tested.
[0087] Test method:
[0088] Light transmittance and haze are tested according to ASTM D1003 standard;
[0089] The center brightness and average brightness are tested according to GY / T 326-2019 standard;
[0090] Impact strength is tested according to GB / T 1043.1-2008 standard;
[0091] Water barrier performance is usually characterized by water vapor transmission rate (GB / T 1037), which is usually measured at 38℃ / 90RH to measure the mass of water vapor permeating through a unit area of the film, in units of g / (m 2 24h);
[0092] The oxygen barrier performance is characterized by oxygen transmission rate (GB / T 1038), which measures and calculates the volume of oxygen that passes through the sample within 24 hours, in cm 3 / (m 2 ·24h·0.1MPa);
[0093] Brightness retention rate test method: Place the quantum dot diffusion plate at 60°C and 90% RH humidity for 1000 hours, detect the brightness values before and after placement, and calculate the brightness retention rate, brightness retention rate = (brightness value after aging / brightness value before aging) * 100%;
[0094] Brightness and color point detection method: Place the quantum dot diffusion plate under the blue light LED module, and use the CA-310 color analyzer to test the center point brightness, color point X, and color point Y. The current is fixed at 174mA and the voltage is fixed at 8.3V. The test results are shown in Table 1.
[0095] Table 1 Diffuser plate performance test results
[0096]
[0097] From the experimental data in Table 1, the quantum dot diffusion plates prepared in each embodiment of the present application have a transmittance of more than 60%, a haze of more than 90%, a central brightness of more than 2000, an average brightness of about 2000, and a brightness retention rate of more than 90%, indicating that each embodiment has high luminous efficiency, good transmittance, and long brightness retention time; the color coordinate X offset and the color coordinate Y offset are excellent, indicating that the luminescence of each embodiment is stable; the water vapor permeability is less than 0.5g / (m 2 ·24h), oxygen permeability coefficient is less than 0.6cm 3 / (m 2 ·24h·0.1MPa), indicating that each embodiment has high water and oxygen barrier properties; the impact strength is greater than 200Kg / cm 2 , indicating that the quantum dot diffusion plates prepared in each embodiment have high impact resistance and good toughness.
[0098] By further comparing and analyzing the data of Example 1 with the comparative example, it is found that after the PBT resin is replaced with GPPS in the process of preparing the intermediate diffusion plate in Comparative Example 1, the surface carboxylation oil-soluble CdSe / ZnS quantum dots have poor biocompatibility with GPPS, resulting in quantum dot clusters, which in turn leads to poor transmittance and unstable luminescence of the comparative example product compared with the product of Example 1; in Comparative Example 2, after the surface carboxylation oil-soluble CdSe / ZnS quantum dots are replaced with ordinary oil-soluble CdSe / ZnS quantum dots in the process of preparing the intermediate diffusion plate, the PEI polymer The coating effect of the polymer microspheres on the oil-soluble CdSe / ZnS quantum dots is poor, which leads to poor transmittance, poor water and oxygen barrier properties, and unstable luminescence of the comparative example product compared with the product of Example 1; since glutaraldehyde is not added in the process of preparing the intermediate diffusion plate in Comparative Example 3, a stable network structure is not formed between the surface carboxylation oil-soluble CdSe / ZnS quantum dots and the PEI polymer microspheres, so that the surface carboxylation oil-soluble CdSe / ZnS quantum dots are not firmly combined with the surface of the PEI polymer microspheres, so the transmittance, haze, and center brightness of Comparative Example 3 are poor. The brightness, average brightness, color coordinate X offset, color coordinate Y offset, water vapor permeability, and oxygen permeability coefficient are slightly worse than those in Example 1, but better than the other comparative data; in the process of preparing the upper and lower diffusion plates, the GPPS resin replaces the PBT resin in Comparative Example 4, which has a certain impact on the transmittance, center brightness, average brightness, and impact strength of the entire quantum dot diffusion plate. This may be because after the GPPS resin replaces the PBT resin, the structure of the upper and lower diffusion plates changes, resulting in a change in the light propagation path, which ultimately affects the reflection, refraction, and scattering effects of the light, thereby causing the overall performance of the quantum dot diffusion plate to deteriorate; in the process of preparing the upper and lower diffusion plates in Comparative Example 5, due to the lack of addition of γ-aminopropyltriethoxysilane, the PBT resin and the PEI polymer microspheres failed to form a three-dimensional network structure, making it impossible for the PEI polymer microspheres to be evenly and stably dispersed in the PBT resin, ultimately resulting in the transmittance, center brightness, and average brightness of the entire quantum dot diffusion plate to deteriorate; from the experimental results, all indicators of Example 1 are better than the mass-produced sample (CPQ18B) on the market, with better comprehensive performance and greater market competitiveness. Figure 1 It can also be further verified that the surface carboxylated oil-soluble CdSe / ZnS quantum dots can be uniformly dispersed in PBT resin after being uniformly coated with PEI polymer microspheres. Figure 2 It can be seen that the maximum decomposition temperature of the quantum dot diffusion plate prepared in this application is 420°C due to thermal weight loss, and it has good heat resistance.
[0099] In summary, the quantum dot diffusion plate provided by the present application includes three layers, upper, middle and lower, which can more effectively disperse and homogenize light. Each layer can scatter light once. Through multi-layer scattering, the distribution of light is more uniform; the middle layer diffusion plate uses PEI polymer microspheres to uniformly coat the surface carboxylated oil-soluble CdSe / ZnS quantum dots to improve the stability of the quantum dots, and improve the fluorescence intensity and quantum yield; by adding the cross-linking agent glutaraldehyde, a stable network structure is formed between the surface carboxylated oil-soluble CdSe / ZnS quantum dots and the PEI polymer microspheres, so that the surface carboxylated oil-soluble CdSe / ZnS quantum dots are more firmly bonded to the surface of the PEI polymer microspheres; and the selected PEI polymer microspheres have good compatibility with the PBT resin, so that the PEI polymer microspheres are more easily evenly dispersed in the PBT resin after uniformly coating the surface carboxylated oil-soluble CdSe / ZnS quantum dots, so that the entire middle layer diffusion plate emits light more uniformly, At the same time, the test found that the refractive index of the quantum dot polymer composite microspheres formed by uniformly coating the surface carboxylated oil-soluble CdSe / ZnS quantum dots with PEI polymer microspheres is 1.5463, which is slightly different from the refractive index of PBT resin of 1.5613. Therefore, the prepared middle-layer diffuser plate can simultaneously obtain higher transmittance and haze; the upper and lower diffuser plates have the same components. The transmittance of the upper and lower diffuser plates is improved by adding PEI polymer microspheres to the PBT resin. At the same time, the addition of γ-aminopropyltriethoxysilane can make the PBT resin and the PEI polymer microspheres cross-linked to form a three-dimensional network structure, so that the PEI polymer microspheres are uniformly and stably dispersed in the PBT resin. In this way, the composition and structure of the upper and lower diffuser plates are completely different from those of the middle-layer diffuser plate. The light passes through the upper, middle and lower diffuser plates in sequence and continuously changes the propagation direction, so that the entire quantum dot diffuser plate can achieve more uniform light distribution, more efficient transmittance and better durability.
[0100] In summary, the quantum dot diffusion plate prepared in this application not only maintains high water and oxygen barrier properties and luminous efficiency, but also has the advantages of stable luminescence, high light transmittance, high mechanical strength, and fatigue resistance. It combines the advantages of quantum dot diffusion plate and PBT resin and has broad application prospects.
[0101] The above is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A quantum dot diffuser plate, characterized in that: It comprises an upper diffuser plate, an intermediate diffuser plate and a lower diffuser plate, wherein the upper diffuser plate and the lower diffuser plate are located on both sides of the intermediate diffuser plate, and the intermediate diffuser plate comprises the following components by mass: 74-88 parts of PBT resin, 1-3 parts of PEI polymer microspheres, 0.1-0.5 parts of surface carboxylation oil-soluble CdSe / ZnS quantum dots, 0.05-0.09 parts of glutaraldehyde, 10-20 parts of ethanol, 0.3-0.7 parts of antioxidants, 0.03-0.07 parts of mineral oil, 0.3-0.7 parts of light stabilizers, 0.2-0.9 parts of ultraviolet absorbers, and 0.02-0.04 parts of brighteners, and the PEI polymer microspheres uniformly coat the surface carboxylation oil-soluble CdSe / ZnS quantum dots; The upper diffuser plate and the lower diffuser plate have the same components, and the upper diffuser plate or the lower diffuser plate includes the following components in parts by mass: 79 to 89 parts of PBT resin, 7 to 11 parts of PEI polymer microspheres, 3 to 7 parts of γ-aminopropyltriethoxysilane, 0.4 to 1.2 parts of antioxidant, 0.03 to 0.07 parts of mineral oil, 0.3 to 0.7 parts of light stabilizer, 0.2 to 0.9 parts of ultraviolet absorber, and 0.07 to 0.13 parts of whitening agent.
2. The quantum dot diffuser plate according to claim 1, characterized in that: The antioxidant is at least one of antioxidant 1024, antioxidant 1010 or antioxidant 1076.
3. The quantum dot diffuser plate according to claim 1, characterized in that: The mineral oil is silicone oil or liquid paraffin.
4. The quantum dot diffuser plate according to claim 1, characterized in that: The light stabilizer is any one or more selected from the group consisting of light stabilizer 622, light stabilizer 770, and light stabilizer 944.
5. The quantum dot diffuser plate according to claim 1, characterized in that: The ultraviolet absorber is selected from one or more of the ultraviolet absorbers UV-327, UV-329, and UV-531.
6. The quantum dot diffuser plate according to claim 1, characterized in that: The whitening agent is fluorescent whitening agent CBS-127.
7. A method for preparing a quantum dot diffusion plate according to any one of claims 1 to 6, characterized in that: The following steps are involved: Add 10-20 parts of ethanol to a reaction container, then add 0.1-0.5 parts of surface carboxylation oil-soluble CdSe / ZnS quantum dots to the ethanol, perform ultrasonic treatment for 10-30 minutes to ensure that the surface carboxylation oil-soluble CdSe / ZnS quantum dots are uniformly dispersed in the ethanol, then mix 1-3 parts of PEI polymer microspheres and 0.05-0.09 parts of glutaraldehyde and add the mixture to the reaction container, stir while adding to ensure that the PEI polymer microspheres uniformly cover the surface carboxylation oil-soluble CdSe / ZnS quantum dots to obtain a mixed solution, centrifuge the mixed solution, collect a precipitate, wash the precipitate with ethanol for multiple times, and then dry the precipitate for standby use; The precipitate is mixed with 74-88 parts of PBT resin, 0.3-0.7 parts of antioxidant, 0.03-0.07 parts of mineral oil, 0.3-0.7 parts of light stabilizer, 0.2-0.9 parts of ultraviolet absorber, and 0.02-0.04 parts of brightener to obtain a mixture a; 79-89 parts of PBT resin, 7-11 parts of PEI polymer microspheres, 3-7 parts of γ-aminopropyltriethoxysilane, 0.4-1.2 parts of antioxidant, 0.03-0.07 parts of mineral oil, 0.3-0.7 parts of light stabilizer, 0.2-0.9 parts of ultraviolet absorber, and 0.07-0.13 parts of brightener are uniformly mixed to obtain a mixture b; The mixture a and the mixture b are put into a single screw extruder for heating and melting, and three-layer co-extrusion and embossing are performed to obtain a finished product; Among them, the temperatures of each zone of the single-screw extruder are: zone one temperature is 190~200℃, zone two temperature is 210~220℃, zone three temperature is 220~230℃, zone four temperature is 220~230℃, zone five temperature is 230~240℃, zone six temperature is 230~240℃, zone seven temperature is 220~230℃, and the die head temperature is 215~225℃.
8. The method for preparing a quantum dot diffusion plate according to claim 7, characterized in that: During the centrifugal separation of the mixed solution, the centrifuge speed is 2000-4000 rpm.
Citation Information
Patent Citations
Polymer-coated perovskite quantum dots and preparation method thereof
CN109306265A
Stable quantum dot extrusion film
CN111094506A